Modification of Harvard step-test for assessment of students’ with health problems functional potentials - E.N. Kopeikina; V.V. Drogomeretsky; V.L. Kondakov; M.V. Kovaleva; S.S. Iermakov (Physical Education of Students, 2016)
Purpose: to substantiate, work out and experimentally prove modified test for assessment of students’ with health problems functional potentials. Material: in the research students and girl students of 18-20 years’ age (n=522) participated. According to the worked out modification of test during 30 seconds student ascended on bench (h=43 cm) and descended from it. Then pulse was measured three times. In total the test took 4 minutes. Results: For working out the scale for interpretation of the received results we assessed new 30 seconds’ modification of Harvard step-test for validity. First, for this purpose all students fulfilled modified step-test. Then after full restoration (after 20 minutes) they fulfilled its three minutes’ variant. Correlation analysis of the received results showed the presence of average correlation between two samples (r=0.64). Conclusions: application of this modified variant permits for pedagogues to completely assess functional potentials of students with heath problems.